The power of the tensor in NLP : using unlabeled data and learning from context (Manning Publications, 2020)
Text Representation: How We Model Language as Tensors" with Chris Mattmann, Deputy CTO at NASA JPL, and Dr. Scott Penberthy, Director of Applied AI at Google, hosted by Dale Markowitz, Applied AI Engineer at Google.